Traditional chinese medicine diet paratherapy for alleviating toxicity in chemotherapy and radiotherapy in cancer patients: a meta-analysis - ZHOU,Xiaoying (2021)
Abstract The aim of this meta-analysis was to evaluate the efficacy of Traditional Chinese Medicine (TCM) diet therapy in alleviating the toxicity of chemotherapy and radiotherapy in patients with cancer. Searches were conducted in seven databases for relevant studies published from 1, January 2000 to 1 March, 2020. Randomized controlled trials (RCTs) comparing TCM diet with ordinary diet of cancer patients undergoing chemotherapy and(or) radiotherapy were included. The study has been registered on the “PROSPERO” website with registration number of CRD42019131232. A total of sixteen RCTs included 2336 cases were included. TCM diet therapy is superior to ordinary diet in terms of reducing incidence of leukopenia [RR= 0.57; 95% CI (0.47, 0.69); P<0.0001], and nausea and vomiting [RR=0.54, 95% CI= (0.43, 0.70), P= 0.004], increasing hemoglobin [MD=10.04; 95% CI (7.66, 12.41); P<0.0001], improving Karnofsky Performance Status (KPS) [RR= 1.28; 95% CI (1.15, 1.42); P<0.0001], and gaining weight [RR=1.53, 95%CI= (1.38, 1.68), P < 0.0001] in patients with cancer undergoing chemotherapy and(or) radiotherapy. This meta-analysis demonstrated that TCM diet may reduce the toxicity of chemotherapy (and/or radiotherapy).